Hubungan Sistem Administrasi Pendaftaran Menggunakan SIMRS dengan Waktu Tunggu Pelayanan Pasien Rawat Jalan di RS Patria IKKT Tahun 2025 - Khoiri Nur Kholis; Ellynia Ellynia; Ria Efkelin (Pusat riset dan Inovasi Nasional, 2025)
Long outpatient waiting time is an indicator of suboptimal hospital administrative systems. The Hospital Management Information System (SIMRS) is designed to improve administrative efficiency; however, in practice, complaints about long patient waiting time still persist. This study aims to examine the relationship between the registration administrative system using SIMRS and the waiting time for outpatient services at RS Patria IKKT in 2025. A quantitative approach with a cross-sectional analytical design was employed. The sample consisted of 100 outpatient respondents selected using purposive sampling. Data were collected through questionnaires and analyzed using the Chi-Square test and Spearman correlation to determine the relationship between variables. The results show that the system quality, information quality, and service quality of SIMRS at RS Patria IKKT are categorized as good. Spearman correlation analysis reveals no significant relationship between system quality (p=0.281) and information quality (p=0.910) to waiting time. However, the Chi-Square test indicats a significant relationship between service quality (p=0.001) and outpatient waiting time. The implementation of SIMRS at RS Patria IKKT contributes to accelerating administrative processes and reducing outpatient waiting time. Nevertheless, improvements in service quality are necessary to achieve more optimal results.